Kings’ and the king’s banquets in some medieval prose and theatre - Maleval, Maria do Amparo Tavares (2014)
This study aims to observe how the food is represented in some works of medieval prose and theater in order to serve the purpose of Christian indoctrination or spread the magnanimity of kings. Such representations will therefore be seen as rhetorical devices, as persuasion techniques in order to serve the purposes of religious conversion or political propaganda.